SYNTHESIS OF RUTILE TIO2 NANOPARTICLES BY CO-PRECIPITATION METHOD - Nazaruddin Nasution; Aida Fitri (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Abstract. The objective of this research is to produce rutile TiO2 nanoparticles by co-precipitation method and to determine its characterization using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), X-ray Diffractometry (XRD), and Particle Size Analysis (PSA) methods. Synthesis of rutile TiO2 nanoparticles by co-precipitation method in this study was initiated by mixing 15% TiCl3 solution into distilled water while stirring at constant speed for some time. Then, pH is adjusted to 11-13 by dripping ammonia (NH4OH) solution while continuing to stir. The precipitate (white gel) is then dried in the oven and crushed to produce TiO2 powder. The morphology of the TiO2 particles obtained is spherical and tends to agglomerate. The average particle size of TiO2 produced is 192.2 nm. The EDS results show that the percentage of Ti mass in TiO2 particles is 59.52%. Based on XRD analysis, there are two phases formed namely anatase and rutile with a tetragonal crystal system.Keywords: Co-precipitation method, nanoparticles, and rutile.